Politeness Language Analysis in Teenagers Reviewed from Sociolinguistics - Muhammad Darwis (BIRCU, 2018)
This study aims to find out and describe data on language politeness among teenagers in Kuala Simpang city, Aceh Tamiang district in terms of sociolinguistics. The appropriate research approach uses in this study is qualitative research. The type of research is field research. The data of this study is the conversation of teenagers of Bukit Tempurung Village, Kuala Simpang City. Data sources are a number of teenagers in Bukit Tempurung Village, Kuala Simpang City. Data collected by recording techniques during social activities, then in manuscripts in the form of conversation. The results showe that there are 6 languages politeness maxims used by teenagers during social activities. Maksim is in the form of wisdom maxims of four (4) data, generosity maxims as much as seven (7) data, award maxims of two (2) data, simplicity maxim of one (1) data, consensus maximization of fourteen (14) data, and the implicit maxim of one (1) data. Based on the research data, the most dominant maxim is the agreement maxim